2014
DOI: 10.1111/fwb.12476
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use effects on terrestrial consumers through changed size structure of aquatic insects

Abstract: Summary We assessed the influence of agricultural land use on aquatic–terrestrial linkages along streams arising from changes in the emergence of aquatic insects. We expected that terrestrial predators would respond to a change in the abundance and/or the size structure of the emerging aquatic insects by an increase or decrease in population size. We measured the flux of emergent aquatic insects and the abundance of terrestrial invertebrate predators and birds along 10 streams across a forest‐to‐agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 53 publications
2
90
0
2
Order By: Relevance
“…Large body size is an indicator of stronger flying strength, and the availability of both larger sized and smaller sized subsidy might allow for optimal feeding across a broader size range of terrestrial consumers (Brose et al 2008). Our finding that longer-lived, larger sized and stronger flying taxa did not differ between forested and agricultural streams emphasises the need to quantify as biomass how much aquatic subsidy these taxa export, compared with much more abundant but weaker flying smaller taxa (Stenroth et al 2015). Significantly, most of the taxa associated with these traits were almost entirely absent in the survey of adult flying insects conducted by Carlson et al (2016), possibly because these taxa are either too large and strong, or fly too high, to be routinely trapped by their sticky trap sampling method.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Large body size is an indicator of stronger flying strength, and the availability of both larger sized and smaller sized subsidy might allow for optimal feeding across a broader size range of terrestrial consumers (Brose et al 2008). Our finding that longer-lived, larger sized and stronger flying taxa did not differ between forested and agricultural streams emphasises the need to quantify as biomass how much aquatic subsidy these taxa export, compared with much more abundant but weaker flying smaller taxa (Stenroth et al 2015). Significantly, most of the taxa associated with these traits were almost entirely absent in the survey of adult flying insects conducted by Carlson et al (2016), possibly because these taxa are either too large and strong, or fly too high, to be routinely trapped by their sticky trap sampling method.…”
Section: Discussionmentioning
confidence: 72%
“…Significantly, most of the taxa associated with these traits were almost entirely absent in the survey of adult flying insects conducted by Carlson et al (2016), possibly because these taxa are either too large and strong, or fly too high, to be routinely trapped by their sticky trap sampling method. It is not known whether dispersal of these taxa is inhibited to the same extent in agricultural landscapes as observed for smaller sized and weak flying Diptera (Carlson et al 2016), though Stenroth et al (2015) notably found that adults of larger sized aquatic taxa were more associated with forested than agricultural streams.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Land use -Almost all ecosystems suffer from some degradation due to impacts of land use, such as by agriculture, urbanization and deforestation or forest harvesting [108,118,119], which were the dominant changes in the past 100 years and seriously impacted biodiversity and ecosystem functioning at local, regional and global scales [120]. During the past 50 years, agricultural land use was and will continue to be the main reason of ecological changes in both aquatic and terrestrial ecosystems [121].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%
“…Trichoptera and Plecoptera) were more related to forest land use, and this size change of prey subsidy is associated with the distribution of different types of terrestrial predators, causing a different terrestrial predator community structure [119]. -Land use can change the magnitude of subsidies, Francis and Schindler (2009) found that at all geographical scales, shoreline development negatively influenced terrestrial invertebrate subsidies, with 100% of the diet of fish were terrestrial insects in undeveloped lakes, whereas it was only 2% in developed lakes [108].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%